How do LGBTQ+ library catalog users talk about subject searching? - Moulaison-Sandy, Heather; Dobreski, Brian; Snow, Karen (Journal of documentation, 2025)
PurposeSubject searching in the library catalog is a challenge for any user, but may be especially so for members of marginalized groups whose language diverges even further from established systems of subject headings. In this study, researchers employed the concept of code-switching to better understand the linguistic divide that members of the LGBTQ+ community face when formulating subject searches in the library catalog.Design/methodology/approachThrough a set of 15 interviews with adult library users identifying as LGBTQ+, researchers examined the difference between participants’ natural language when discussing books and their suggested search terms for these same items. Analysis of language switching was guided by a linguistic framework of semantic, syntactic and lexical elements.FindingsResults show that LGBTQ+ catalog users employ linguistic shifts when approaching the library catalog, particularly semantic shifts around terminology for genres and LGBTQ+ identities. Almost all participants were aware of their language switching to some extent, with many purposely employing it in an anticipatory attempt to match their perceptions of the catalog’s language.Social implicationsFor libraries looking to better support marginalized communities, this study offers insight into the linguistic perceptions and practices of these users and the disconnect they may face when searching for resources related to their identities. Pluralistic approaches to subject representation may offer one means of addressing this.Originality/valueThis study takes the novel approach of applying the concept of code-switching to better understand the needs and perceptions of library catalog users.